Immunomodulatory Properties of Bacterium-Like Particles Obtained From Immunobiotic Lactobacilli: Prospects for Their Use as Mucosal Adjuvants - Raya Tonetti, Fernanda; Arce, Lorena; Salva, Susana; Alvarez, Susana; Takahashi, Hideki; Kitazawa, Haruki; Vizoso-Pinto, Maria Guadalupe; Villena, Julio (Frontiers in Immunology, 2020)
Non-viable lactic acid bacteria (LAB) have been proposed as antigen delivery platforms called bacterium-like particles (BLPs). Most studies have been performed with Lactococcus lactis-derived BLPs where multiple antigens were attached to the peptidoglycan surface and used to successfully induce specific immune responses. It is well established that the immunomodulatory properties of LAB are strain dependent and therefore, the BLPs derived from each individual strain could have different adjuvant capacities. In this work, we obtained BLPs from immunomodulatory (immunobiotics) and non-immunomodulatory Lactobacillus rhamnosus and Lactobacillus plantarum strains and comparatively evaluated their ability to improve the intestinal and systemic immune responses elicited by an attenuated rotavirus vaccine. Results demonstrated that orally administered BLPs from non-immunomodulatory strains did not induce significant changes in the immune response triggered by rotavirus vaccine in mice. On the contrary, BLPs derived from immunobiotic lactobacilli were able to improve the levels of anti-rotavirus intestinal IgA and serum IgG, the numbers of CD24+B220+ B and CD4+ T cells in Peyer´s patches and spleen as well as the production of IFN- by immune cells. Interestingly, among immunobiotics-derived BLPs, those obtained from L. rhamnosus CRL1505 and L. rhamnosus IBL027 enhanced more efficiently the intestinal and systemic humoral immune responses when compared to BLPs from other immunobiotic bacteria. The findings of this work indicate that it is necessary to perform an appropriate selection of BLPs in order to find those with the most efficient adjuvant properties. We propose the term Immunobiotic-like particles (IBLPs) for the BLPs derived from CRL1505 and IBL027 strains that are an excellent alternative for the development of mucosal vaccines.